Food safety risk profiling of cadmium in the consumption of squid in the Philippines - Dela Cruz, Denise Anne B.
Cadmium (Cd) is an element that is ubiquitously found in low concentrations in the environment. Anthropogenic activities are reported to increase its levels and contaminate marine environment. When ingested, Cd can be harmful to the human body and is associated with different kinds of cancer, various diseases, and even death. Particularly, squid is a commodity vulnerable to Cd contamination due to its ability to bioaccumulate. In this study, the risk profile of Cd in squids consumed in the Philippines was established that included information on the data gaps in the risk profiling process, estimated dietary exposures (DE) of the Filipino consuming population, and available risk management options in controlling Cd in squid. Data on the average (x̄) Cd concentration in squid samples (n=495) obtained from Luzon (Regions 1, 4B, and 5), Visayas (Regions 6 and 8), and Mindanao (Regions 12 and 13) ranged from 0.07-2.07 mg/kg, with the highest Cd concentration recorded in Region 6 (2.07 mg/kg) that exceeded the ML of 2.0 mg/kg (PNS 136:2013; CODEX STAN 193:1995). Dietary exposure (DEs) calculated using average (x̄) Cd concentrations showed that only Regions 4B, 6 and 12 exceeded 100% of the PTMI (25 μg/kg bw/month) established by JECFA (2010). However, when maximum concentrations were used, DE values exceeded the PTMI for all age groups in all regions except for NCR and Region 13. Among all age groups, infants and pre-school children are the most vulnerable. In addition, females were generally observed to have higher DEs than males. These findings indicate that there is an appreciable health risk in the consumption of squids by the Filipino population, especially among Filipinos under 18 y, due to the exceedance of 100% of the established PTMI.